10 Years of "Ankole sacred music" in the Diocese of Mbabara - Van Thiel, Paul (International Library of African Music, 1965)
In Uganda, the very first attempts to introduce Sacred Music in African style into divine worship were made in the Diocese of Mbabara (West Uganda) in the year 1955. were made in the Diocese of Mbabara (West Uganda) in the year 1955. During the initial stage the experiments did not meet with the approval of everybody. The same has been experienced in various other African countries. Therefore a Musical Study Week was held at Mbabara during the Easter holidays in 1959 and was attended by over 50 musical Banyankore, lay- people as well as religious. Many different musical problems were dealt with, but of course special attention was given to producing Ankole Sacred Music and the possibility of introducing it into the Liturgy.
Keywords: African Music